2021
DOI: 10.1186/s12889-021-12289-0
|View full text |Cite
|
Sign up to set email alerts
|

The burden of mental health illnesses in Kerala: a secondary analysis of reported data from 2002 to 2018

Abstract: Background The burden of mental health in India, as in other Low- and Middle-Income Countries (LMICs), is substantial. Secondary Analysis of survey data provides insight into trends in mental health morbidity over time, while administrative data can indicate corresponding trends in availability of infrastructure and services. We compared data from three national level surveys conducted in India to analyse trends in mental health morbidity and available institutional mechanisms to address mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This has been called the 'Kerala Model' of development, characterised by a Human Development Index (HDI) comparable to developed nations, high literacy, quality primary health care services, and low maternal mortality (Parayil 2000). In spite of past achievements, the state has recently reported increased mental morbidity, along with inadequate infrastructure and human resources to address this issue (Joseph, Hari Sankar, and Nambiar 2021;Shibukumar and Thavody 2017). The state has responded with projects aimed at addressing specific issues such as maternal mental health and adolescent mental health.…”
Section: Introductionmentioning
confidence: 99%
“…This has been called the 'Kerala Model' of development, characterised by a Human Development Index (HDI) comparable to developed nations, high literacy, quality primary health care services, and low maternal mortality (Parayil 2000). In spite of past achievements, the state has recently reported increased mental morbidity, along with inadequate infrastructure and human resources to address this issue (Joseph, Hari Sankar, and Nambiar 2021;Shibukumar and Thavody 2017). The state has responded with projects aimed at addressing specific issues such as maternal mental health and adolescent mental health.…”
Section: Introductionmentioning
confidence: 99%
“…27 A study regarding the burden of MI in Kerala has found that the number of individuals with mental illness in Kerala increased from 272 persons per lakh to 400 persons per lakh in the time period of 2002 to 2018. 28 Even though studies have been done among the caregivers and college students to evaluate the knowledge, attitude and behaviors towards patients with MI, the tools for assessing the community attitude towards MI are not available in the local language, Malayalam. A validated and reliable Malayalam tool is an essential prerequisite for assessing the level of stigma towards MI.…”
mentioning
confidence: 99%
“…Kerala is also lagging behind other nations in terms of the availability, scope, and calibre of mental health care providers. According to a study by Joseph, Sankar, and Nambiar (2021), Kerala saw a sharp increase in mental health morbidity between 2002 and 2018. This increase is likely the result of a variety of social trends, including more nuclear families, loneliness, and divorce, as well as unemployment, gender inequality, economic migration, pressure on students, addiction, and other factors.…”
Section: Study Contextmentioning
confidence: 99%
“…This increase is likely the result of a variety of social trends, including more nuclear families, loneliness, and divorce, as well as unemployment, gender inequality, economic migration, pressure on students, addiction, and other factors. Infrastructure and human resources appear to be getting better, although they are still judged inadequate at this time (Joseph et al, 2021).…”
Section: Study Contextmentioning
confidence: 99%